THE RIGHT TOOLS FOR THE JOB: THE RIGHT JOB FOR OUR TOOLS - Poovey, Mary (The Nordic Journal of Aesthetics, 2020)
This article ponders the questions of why so many literary scholars want to bring literary and economic issues together now, and why it seems so difficult to establish a genuinely cross-disciplinary con-versation.1 Offering two examples of approaches to the intersec-tion of literary and economic issues that privilege methodology over themes, history, or theory—a very brief genealogy of the concept of a national economy and an equally brief analysis of derivatives—the article calls for an ongoing reflection on whether literary and cultural scholars have the right tools for the job and, conversely, the right job for our tools.